Engineering a carbohydrate binding module to enhance chitinase catalytic efficiency on insoluble chitinous substrate. (1st September 2021) - Su, Haipeng; Gao, Li; Sun, Jianan; Mao, Xiangzhao
Graphical abstract: Highlights: Three chitinase SaChiA4 variants were acquired by modifying the chitin-binding domain. The different recombinant chitinase SaChiA4 variants were purified and characterized. The substitution variant increased its activity by nearly 54% towards chitin powder. ChBD plays an important role in the binding of chitinase to insoluble chitin substrate. ChBD improved the catalytic efficiency by promoting substrate affinity. Abstract: Development of a high-performance chitinase for efficient biotransformation of insoluble chitinous substrate would be highly valuable in industry. In this study, the chitin-binding domains (ChBDs) of chitinase SaChiA4 were successfully modified to improve the enzymatic activity. The engineered substitution variant R-SaChiA4, which had the exogenous ChBD of chitinase ChiA1 from Bacillus circulans WL-12 (ChBDChiA1 ) substituted for its original ChBDChiA4, increased its activity by nearly 54% (28.0 U/mg) towards chitin powder, and by 49% towards colloidal chitin, compared with the wild-type. The substrate-binding assay demonstrated that the ChBD could enhance the capacity of enzymatic hydrolysis by promoting substrate affinity, and molecular dynamics simulations indicated that this could be due to hydrophobic interactions in different substrate binding modes. This work advances the understanding of the role of the ChBD, and provides a step towards the achievement of industrial-scale hydrolysis and utilization of insoluble chitin.